2004
DOI: 10.1065/lca2004.12.181.9
|View full text |Cite
|
Sign up to set email alerts
|

Waste Treatment and Assessment of Long-Term Emissions (8pp)

Abstract: Conclusion.The disposal phase should by default be included in LCA studies. The use of a material not only necessitates its production, but also requires its disposal. The created inventories and user tools facilitate heeding the disposal phase with a similar level of detail as production processes. The risk of LCA-based decisions shifting burdens from the production or use phase to the disposal phase because of data gaps can therefore be diminished. Recommendation and Perspective.Future improvements should in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 8 publications
1
69
0
Order By: Relevance
“…Our results suggest that the selection of such a short time horizon would result in a significant proportion of emissions being unaccounted, which supports the findings of previous researchers (e.g. Doka and Hischier, 2004;Hauschild et al, 2008). If LCA is to be used to provide useful information on the long term impacts of landfilling then a time horizon of 100 years is insufficient.…”
Section: The Use Of Life Cycle Assessmentsupporting
confidence: 78%
“…Our results suggest that the selection of such a short time horizon would result in a significant proportion of emissions being unaccounted, which supports the findings of previous researchers (e.g. Doka and Hischier, 2004;Hauschild et al, 2008). If LCA is to be used to provide useful information on the long term impacts of landfilling then a time horizon of 100 years is insufficient.…”
Section: The Use Of Life Cycle Assessmentsupporting
confidence: 78%
“…Furthermore, waste treatment processes show a relatively high uncertainty for global warming and toxicity. This is caused by nonenergy related emissions, such as methane air emissions and longterm heavy metal leaching from land fills (38).…”
Section: Discussionmentioning
confidence: 99%
“…However, while it is well-recognised that the release of metals from ashes may potentially continue over many thousands of years (e.g. Astrup et al, 2006;Doka and Hischier, 2005), no consensus methodology has yet been found (Laner, 2009). Thus, in this study, long-term emissions (beyond the initial 100-year period) were excluded and the focus was placed on assessing the more immediate environmental consequences.…”
Section: Release Of Toxic Substances During Mswi Ba Utilisationmentioning
confidence: 99%